2017
DOI: 10.1186/s12879-017-2328-6
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution characteristics of multiple human papillomavirus in women from the Taihu River Basin, on the coast of eastern China

Abstract: BackgroundThere is limited data on the genotype distribution of human papillomavirus (HPV) in the Taihu River Basin, home to 1.29 million people on the coast of eastern China. This study evaluated the prevalence and genotypes among different female age groups in this region.MethodsTwenty-six HPV strains (low-risk HPV 6, 11, 40, 42, 44, 61, 73 and high-risk HPV 16, 18, 26, 31, 33, 35, 39, 45, 51, 52, 53, 55, 56, 58, 59, 66, 68, 82, and 83) were detected using Tellgenplex™ HPV technology in samples obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…In China, the bimodal curve of age‐specific HPV distribution is still controversial . In our report, for women aged 55 years or older, the hr‐HPV prevalence was 88.0% and 78.6% among HSIL and ICC patients, respectively, but there was no statistical difference in the overall age‐specific HPV/hr‐HPV distribution.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In China, the bimodal curve of age‐specific HPV distribution is still controversial . In our report, for women aged 55 years or older, the hr‐HPV prevalence was 88.0% and 78.6% among HSIL and ICC patients, respectively, but there was no statistical difference in the overall age‐specific HPV/hr‐HPV distribution.…”
Section: Discussioncontrasting
confidence: 46%
“…In China, the bimodal curve of age-specific HPV distribution is still controversial. 27,28 In our report, for women aged 55 years or older, the hr-HPV prevalence was 88.0% and 78.6% among HSIL and…”
Section: Discussionmentioning
confidence: 42%
“…The epidemiologic characteristics of HPV genotypes vary by age, ethnicity, geographic location, and socioeconomic status. The “two‐peak pattern” of hrHPV infection among the different age group of women had been reported previously, while it is not common in several other studies in China . Some studies have shown that women younger than 25 years and older than 50 years were observed to be two of the most sensitive groups to hrHPV infection, while the shape of the pattern differs geographically.…”
Section: Introductionmentioning
confidence: 52%
“…in Sichuan, which was lower than that of a previous study conducted in Sichuan (31.5%). 14 It is still controversial whether the age-specific HPV distribution presents a bimodal curve (two-peak pattern) [4][5][6] in Mainland China. In our study, we observed a bimodal curve just like a U-shape in the overall age-specific HPV distribution.…”
Section: Discussionmentioning
confidence: 99%
“…More than 100 genotypes of HPV have been identified, and around 20 distinct HPV types have been associated with cervical carcinoma [14]. Depending on the oncogenic potential, HPV genotypes are categorized into high-risk types, which include HPV 16,18,31,33,35,39,45,51,52,56,58,59,68,69,73, and 82, and low-risk types, which include HPV 6,11,42,43,and 44 [15]. High-risk types of HPV are considered the main risk factors for cervical cancer, with HPV 16 being the most prevalent type in women with normal cytology and women with cervical carcinoma or CIN, whereas low-risk types such as HPV 6 and 11 generally only cause benign lesions or have been rarely associated with cervical carcinoma [1,16,17].…”
Section: *Corresponding Authormentioning
confidence: 99%